Acute myeloid leukemia with monocytic differentiation: a case report - Huerto, José L. (2023)
We present a case of acute monocytic leukemia with monocytic differentiation in a 58-year-old male patient, who was admitted for emergency care at the Alberto Sabogal Sologuren National Hospital. The clinical and laboratory findings of the particular case are described, with emphasis on cytomorphology and immunophenotype. Likewise, a general presentation of the disease is made and, since it is a rare hematologic neoplasm, recommendations for its identification and reporting from the laboratory are proposed.